The Effectiveness of Family Support Program based on Clean and Healthy Behaviour (CLHB) Indicators - Rochana Ruliyandari; Bambang Purwanto; AA Subiyanto; Suwarto (Indian Journal of Forensic Medicine & Toxicology, 2022)
A clean and healthy lifestyle behavior (CHLB) in the household structure is essential to maintain and improve the health of family members. However, in its implementation, consistency is needed so that clean and healthy lifestyle behavior can be carried out optimally based on ten indicators of a CHLB of household arrangements that the government has set. Therefore, this research was conducted using a cross-sectional design with a quantitative descriptive study design—population in the sub-district of Banguntapan, Bantul District, consisting of 826 households. The sample of this study was collected using a technique with a random sampling sample of 100 families and data collection using primary data and secondary data, and field observations. Based on the ten indicators of a clean and healthy lifestyle in the household structure, four indicators have not been appropriately implemented, namely giving exclusive breastfeeding (21%), weighing babies and toddlers every month (14%), doing physical activities every day (34%), and not smoking in the home (23%), with clean and healthy lifestyle coverage in the excellent category (66%). Therefore, it can be concluded that the application of a clean and healthy lifestyle in the Banguntapan, Bantul, household characteristics is good (66%) but has not met the government’s target because four indicators of a clean and healthy lifestyle have not been implemented optimally.